Isolation of Phosphate-Solubilizing Fungi from Forest Soils of the Harau Valley - Roza Yolanda; Dezi Handayani; Azwir Anhar; Irdawati Irdawati (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
The decline in the quality of agricultural products due to nutrient deficiencies such as phosphate is a major problem for agriculture in Indonesia. Technological advances have produced a way to overcome phosphate availability, namely by using phosphate-solubilizing fungi. Organic acids produced by phosphate-solubilizing fungi help reduce phosphate binding in the soil. This study aims to determine the activity of phosphate-solubilizing fungi isolated from Harau Valley Forest soil. Soil sampling was done by the purposive sampling method. The sampling area was along the Aka Barayun Forest in the Harau Valley. Isolation of fungi was carried out using the multilevel dilution method and poured on PDA medium. The fungus activity test was carried out using Pikovskaya media. Based on the results of the study, 6 isolates were obtained, 3 of which had phosphate solubilizing activity, as indicated by the formation of a clear zone around the fungal colonies. Fungal isolates were measured for colony zone diameter, clear zone diameter, and phosphate solubility index (IKF). The isolate with the highest activity was isolate T1, with an IKF of 1.0. The ability to dissolve phosphate of the fungal isolates obtained was categorized as low.